Improving middle school students' proportional reasoning through STEM activities - Nida Sultan Gündoğdu; Mutlu Pişkin Tunç (Journal of Pedagogical Research, 2022)
The aim of this study was to examine the proportional reasoning skills of seventh-grade students before and after the implementation of STEM activities involving proportional and non-proportional relationships. Case study, one of the qualitative study methods, was used in the research. The data for the study was obtained from eight students. Seven different STEM activities were implemented over a seven-week period. A Proportional Reasoning Test and semi-structured interviews were used as data collection tools before and after the implementation of STEM activities. The findings revealed that the STEM activities contributed to the development of students' proportional reasoning skills. Before the STEM activities, students mostly used a cross-multiplication strategy to solve proportional problems. Moreover, they had difficulties in solving numerical comparison and qualitative reasoning problems. Additionally, students frequently used multiplicative relations in non-proportional problems. After the STEM activities, students used multiplicative relations to solve proportional problems. Furthermore, students could solve numerical comparison and qualitative reasoning problems.